Analisis Laporan Kinerja Instansi Pemerintah (LKjIP) Berdasarkan Permenpan RB Nomor 53 Tahun 2014 pada Dinas Kebudayaan dan Pariwisata Kabupaten Toraja Utara - Herlin Tangdilassu; Jenny Morasa; Peter Kapojos (Universitas Sam Ratulangi, 2023)
The Performance Report is an overview that explains concisely and completely about the performance achievements prepared based on the work plan stipulated in the framework of implementing the APBD (PP 6/2006). The purpose of this research is to 1) analyze and find out the performance achievements of the North Toraja Regency Culture and Tourism Office in terms of performance agreement elements based on Permenpan RB Number 53 of 2014; 2) analyze and find out the achievements of the performance report of the North Toraja Regency Culture and Tourism Office in terms of performance reporting elements based on Permenpan RB Number 53 of 2014. The type of research used is qualitative research with a descriptive approach. The results showed that the performance achievements of the North Toraja Regency Culture and Tourism Office were mostly achieved and categorized as successful. And the Government Agency Performance Report (LKjIP) of the North Toraja Regency Culture and Tourism Office has mostly been prepared in accordance with Permenpan RB Number 53 of 2014, but there are still elements in the LKjIP preparation format that are not in accordance with the regulations.